Precision and Accuracy of Thyroid Dysfunction Questionnaire (TDQ) for Hyperthyroidism Screening in Childbearing Age Women - -, Mutalazimah; Mulyono, Budi; Murti, Bhisma; Azwar, Saifuddin (Indonesian Journal of Medicine, 2016)
Background: Community-based case finding efforts of hyperthyroidism rather not to do, but constrained because accurate markers measurements using hormones.Â  TDQ as a screening inÂstrument which meets several criteria for diagnostic tests, provide more convenience for the patient, cheaper, easier and simpler. This study aimed to determine the precision and accuracy of the diagnostic test of hyperthyroidism screening in childbearing age women.Subjects and Method: The study was a diagnostic study with the cross-sectional design. It conducted in Prambanan, Sleman, Yogyakarta. The sample consisted of 112 randomly selected of childbearing age women. Clinical symptoms of hyperthyroidism were measured using the TDQ, thyroid status measured by thyroid stimulating hormone (TSH) and free thyroxin (FT4). TDQ diagnostic precision and accuracy were tested using the percent agreement (PA), Kappa coefficient, sensitivity (Se), specificity (Sp), LR (+), LR (-), Youdenâs index, the area under the curve (AUC) in the receiver operating curve (ROC) and diagnostic odds ratio (DOR).Results: The best value in diagnostic precision is TDQ score with the cutoff point score of 40, with PA 81.2 % and Kappa coefficient 0.62. Similarly, the best accuracy value Se 90%, Sp 76%, LR(+) 3.75, LR(-) 0.13, Youdenâs index 0.66, AUC 0.831 and DOR 28.8.Conclusion: The values and the optimal accuracy obtained from the best score of 40 and this cut off point of the score is sufficient to be used as a threshold determination of a diagnosis of hyperthyroidism by TDQ scores. Keywords: diagnostic tests, thyroid dysfunction questionnaire (TDQ), hyperthyroidism, childÂbearing age women.Correspondence:Â Mutalazimah. Department of Nutritional, Muhammadiyah University of SurakartaIndonesian Journal of Medicine (2016), 1(1): 34-43https://doi.org/10.26911/theijmed.2016.01.01.05